CBR METHOD EXPERT SYSTEM FOR FEMALE REPRODUCTIVE HEALTH PROBLEM DETECTION - Ade Dili Lestari; Iqbal Kamil Siregar; Santoso Santoso (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Technological developments open up opportunities to improve health services, especially in the diagnosis of female reproductive health problems. This research discusses the development of an expert system at Utama General Hospital in Kisaran to assist in the early diagnosis of female reproductive diseases. The problems that occur in this article are the absence of knowledge about dangerous diseases, lack of awareness of reproductive health diseases, remote and hard-to-reach locations of health facilities, high costs for consultations and drugs, and long time to get diagnostic results. The method used in solving these problems is Case Based Reasoning (CBR), where the system uses the experience of previous cases to handle new cases. The process involves collecting patient data, building a knowledge base, and developing an expert system using the CBR approach. Test results show the system is able to provide accurate diagnosis based on the symptoms inputted by the user. Solutions for each disease are displayed, providing useful information for further treatment. In conclusion, the development of this expert system is expected to improve the accessibility and quality of women's reproductive health services by providing fast and appropriate solutions. Keywords: case based reasoning (CBR) method; expert system; main public hospital kisaran; women's reproduction.  Abstrak: Perkembangan teknologi membuka peluang untuk meningkatkan layanan kesehatan, terutama dalam diagnosis masalah kesehatan reproduksi wanita. Artikel ini membahas pengembangan sistem pakar di Rumah Sakit Umum Utama Kisaran untuk membantu diagnosis dini penyakit reproduksi wanita. Masalah yang terjadi pada penelitian ini yaitu Tidak adanya pengetahuan tentang penyakit berbahaya, kurangnya kesadaran akan penyakit kesehatan reproduksi, lokasi fasilitas kesehatan yang terpencil dan sulit dijangkau, biaya tinggi untuk konsultasi dan obat, serta waktu yang lama untuk mendapatkan hasil diagnosa. Adapun metode yang digunakan dalam menyelesaikan masalah tersebut adalah Case Based Reasoning (CBR), di mana sistem menggunakan pengalaman kasus sebelumnya untuk menangani kasus baru. Proses melibatkan pengumpulan data pasien, pembentukan basis pengetahuan, dan pengembangan sistem pakar menggunakan pendekatan CBR. Hasil pengujian menunjukkan sistem mampu memberikan diagnosis akurat berdasarkan gejala yang diinputkan oleh pengguna. Solusi untuk setiap penyakit ditampilkan, memberikan informasi yang berguna untuk penanganan lebih lanjut. Kesimpulannya, pengembangan sistem pakar ini diharapkan meningkatkan aksesibilitas dan kualitas layanan kesehatan reproduksi wanita dengan memberikan solusi yang cepat dan tepat. Kata kunci: metode case based reasoning (CBR); reproduksi wanita; rumah sakit umum utama kisaran; sistem pakar.